A new species of Maera Leach, 1814 and new records of Ceradocus Costa, 1853 and Dulichiella Stout, 1912 (Amphipoda: Hadzioidea) from Laje de Santos, São Paulo State, southeastern Brazil - Queiroz, Beatriz; Senna, André R.; Silva, Alexandre R. Da (Zootaxa, 2025)
A new species of the genus Maera Leach, 1814 is described from the southeastern Brazilian coast. The new species differs from its congeners by presenting (1) gnathopod 1 with serrated palm and dactylus nail present; (2) gnathopod 2, palm with two triangular processes near the dactylus articulation, the latter with 14 setae on the outer margin; (3) pereopod 5, dactylus nail with one subapical spine; (4) and pereopods 6–7, dactylus nail with two subapical spines. An identification key to world species of the genus Maera is also provided. We also present the first record of two other hadzioid species, Ceradocus (Denticeradocus) sp. and Dulichiella anisochir (Krøyer, 1845), for the Marine State Park of Laje de Santos.